2014
DOI: 10.1094/cchem-10-13-0222-r
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Structural, and Thermal Properties of Starch Nanocrystals Affected by Different Botanic Origins

Abstract: Cereal Chem. 91(4):383-388Six types of starch nanocrystals were prepared from corn, barley, potato, tapioca, chickpea, and mungbean starches with an acid hydrolysis method. The yields and morphological, structural, and thermal properties of starch nanocrystals were characterized. Starch nanocrystals had yields ranging from 8.8 to 35.7%, depending on botanical origin. During acid hydrolysis, amylose was effectively degraded, and no amylose was detected in any starch nanocrystal. Shape and size of native starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 26 publications
5
19
0
1
Order By: Relevance
“…In all the cases a weak broad feature is also observed. All those peaks and the pattern suggest that starch and starch nanocrystals obtained are having A‐type crystalline structure . This is in agreement with the reports that starch and starch nanocrystals from cereals are in general having A‐type crystalline structure .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In all the cases a weak broad feature is also observed. All those peaks and the pattern suggest that starch and starch nanocrystals obtained are having A‐type crystalline structure . This is in agreement with the reports that starch and starch nanocrystals from cereals are in general having A‐type crystalline structure .…”
Section: Resultssupporting
confidence: 91%
“…Onset temperature (T o ), peak temperature (T p ), completion temperature (T c ), and enthalpy of melting process (ΔH) were measured from DSC curves and the results are given in Table . In the present study, the maximum of the endothermic peak ranged between 110 and 150 °C, which is consistent with a previous study by Xu et al The temperature range is less than the reported values for the theoretical melting point of dry crystallites which is estimated at 160–210 °C . This is due to the presence of residual moisture in the samples considered.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…3(a), SS shows the characteristic 'A' type crystalline pattern similar to that shown by other grains 22 . SS exhibited strong intensity peak at 17.8°, 23.1° and two weak intensity peaks at 15.1° and 19.8°.…”
Section: X-ray Diffraction Analysissupporting
confidence: 57%